Comparative Study of Physico-chemical Characteristics of Cornhusk Fibre with Cotton - KAMBLI, NISHANT; DESHMUKH, R. R.; BASAK, S.; PATIL, P. G.; MANDHYAN, P. K.; RAJA, A. S. M.; ARPUTHRAJ, A. (Cotton Research Journal, 2021)
In this study good quality ligno-cellulosic fibres were extracted from the cornhusks using an alkaline (NaOH) treatment. Conditions for extraction such as concentration of alkali and temperature were optimized. Physico-chemical properties of the corn husk fibres have been scientifically compared with other important natural cellulosic fibre, cotton. SEM was used to study the morphological structure of cornhusk fibre. FTIR analysis revealed that the cornhusk fibre has similar functional group like cotton. This paper also discusses the feasibility of blending corn husk fibre with cotton fibre.